Parallel processing studies and measurements and improvements of the FIT computing infrastructure - Jóhann Friðriksson (2006)
Verkefnið er opið nemendum og starfsfólki Háskólans á Akureyri This describes the parallel processing studies I have been doing, describes and discusses the computing infrastructure of the faculty of information technology at the University of Akureyri, and covers information about a Beowulf cluster computer which was assembled as a part of this project. This paper not only a part of my dissertation, it is also supposed to serve as a manual for those who would like to utilize the FIT systems to perform computations as in their coursework or research.